(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
There is no room for debate over the rising importance ofservices in today’s world. This has been established well in the previouschapter on review of literature by various researchers over the time. Theservice sector dominates the economies world over. India is no exception. We asa nation are developing and being active members in the world trade, we need toknow the rules of the game. Presently, the Indian service sector is in adeveloping state. The competition at such stages ought to be intense. Toachieve a competitive advantage companies, are striving hard to developcompetencies. The capabilities in the form of human resources are a must forevery firm focusing on providing quality services to secure a competitive edge.The human resource practices of a firm and employees behaviour may affect thequality of services. Moreover, it is imperative for any organization to providequality services to secure customer loyalty which is important for the firmperformance.